Pengaruh Jenis Bahan Pengkaya dan Takaran Kompos Biochar terhadap Pertumbuhan dan Hasil Jagung (Zea mays L) dalam Tumpangsari dengan Kacang Hijau (Vigna radiata L) di Tanah Entisol Semiarid - Alfridus Klau (Savana Cendana, 2020)
The aim of the study was to determine the response of the type of enrichment material and the dose of biochar compost to the growth of maize in intercropping with mung bean in entisol semiarid soil. The research was carried out from June to October 2019 in the experimental garden of the Faculty of Agriculture, University of Timor, Sasi Village, Kota Kefamenanu District, Timor Tengah Utara Regency, Nusa Tenggara Timur Province. The design used in this study was a 3 x 3 strip plot design which was repeated 3 times. The first faktor is biochar compost which consists of 3 levels, namely: pure biochar, biochar compost + chicken manure, and biochar compost + cow dung. Meanwhile, in the second faktor, the compost rates were 0 t/ha, 5 t/ha and 10 t/ha. The results showed that the treatment of the type of biochar with the dose did not occur interaction. The level of treatment of biochar compost was not significantly different in all parameters observed, while the dose of biochar compost was significantly different with the treatment level of 10 t/ha which resulted in the best environmental conditions, growth and yields.